Rise of AI: Transforming Data Analytics in Marketing Strategies - Mohamad Sajili; Lintang Anis Bena Kinanti; Andi Muhammad Rudhan (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study investigates the transformative impact of AI technology and data analytics on marketing strategies within PT. Lautan Luas Tbk, a leading chemical distribution and manufacturing company. Through a quantitative research design, employing random sampling of 100 consumers and utilizing Smart PLS for analysis, the study examines the relationships between AI Technology Implementation, Data Quality and Availability, Analytical Capabilities, and Marketing Performance. The findings reveal significant direct effects, indicating that both AI Technology Implementation and Data Quality and Availability positively influence Analytical Capabilities and Marketing Performance. Moreover, significant indirect effects highlight the mediating role of Analytical Capabilities in the relationship between AI Technology Implementation / Data Quality and Availability and Marketing Performance. These results underscore the critical importance of adopting advanced data analytics and AI technologies, as well as ensuring data quality and availability, in enhancing marketing performance. The implications suggest that investments in AI technology integration and data management practices are essential for driving effective marketing strategies and achieving sustainable business growth in the competitive landscape of the chemical industry.